2022
DOI: 10.2196/36794
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility, Acceptability, and Preliminary Outcomes of a Cognitive Behavioral Therapy–Based Mobile Mental Well-being Program (Noom Mood): Single-Arm Prospective Cohort Study

Abstract: Background The prevalence of anxiety, depression, and general distress has risen in recent years. Mobile mental health programs have been found to provide support to nonclinical populations and may overcome some of the barriers associated with traditional in-person treatment; however, researchers have voiced concerns that many publicly available mobile mental health programs lack evidence-based theoretical foundations, peer-reviewed research, and sufficient engagement from the public. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 85 publications
0
4
0
Order By: Relevance
“…We did not measure factors like usability or acceptability of the program in this study, but these factors could also explain the high level of maintenance achieved, as research on another Noom program showed high levels of usability and acceptability. 48 The Noom programs have utilized user experience research and experimentation to increase usability, which could amplify engagement and weight loss management more than alternatives with less usability and acceptability. Future research should assess how usability and acceptability directly influence engagement and maintenance.…”
Section: Discussionmentioning
confidence: 99%
“…We did not measure factors like usability or acceptability of the program in this study, but these factors could also explain the high level of maintenance achieved, as research on another Noom program showed high levels of usability and acceptability. 48 The Noom programs have utilized user experience research and experimentation to increase usability, which could amplify engagement and weight loss management more than alternatives with less usability and acceptability. Future research should assess how usability and acceptability directly influence engagement and maintenance.…”
Section: Discussionmentioning
confidence: 99%
“…The sample size was determined based on an estimated medium effect on post-intervention scores on our primary outcome, the GAD-7, from baseline to end of program, 95% power, and α set at 0.05. The effect size is based on an ITT analysis of the GAD-7 (d=0.70) from a previous Noom Mood feasibility study [24]. The sample size calculation was conducted using G*Power [29] matched pairs t tests.…”
Section: Power Analysis and Sample Size Calculationmentioning
confidence: 99%
“…All surveys were administered online via OpenClinica, a HIPAA-compliant electronic data capture platform [32]. 280 participants eligible [24].…”
Section: Recruitment and Eligibilitymentioning
confidence: 99%
See 1 more Smart Citation